Between Democracy and Technocracy: The Paradox of the functioning of the European Committee of the Regions - Paweł Bącal (Facta Simonidis)
The aim of the present paper is to analyse the consequences of the construction of membership in the European Committee of the Regions. To be a member of this body, one must have a democratic mandate at a local or regional level. This should bring the citizens closer to the European Union and therefore, reduce the democratic deficit. However, it all depends on the actual model of the functioning of the European Committee of the Regions. In practice, it can be described as technocratic rather democratic, which is a great paradox. Such a conclusion has been drawn on the basis of the author’s own empirical research.